Acoustic characterization of the threatened bat Neoeptesicus innoxius (Chiroptera: Vespertilionidae) and two sympatric species in western Ecuador - Restrepo-Giraldo, Carlos (2026)
Introduction: Bioacoustics allows the study of the ecology and behavior of bats through the analysis of echolocation signals. In insectivorous bats, foraging strategies, prey preference, and habitat use are closely related to the emission patterns of echolocation signals. Identifying significant bat habitats and improving conservation efforts can benefit from understanding these relationships. Objectives: To describe the echolocation signals of an endangered species Neoeptesicus innoxius, and other commonly detected species in the study area, Myotis nigricans and Molossus molossus, to contribute to the construction of a bat echolocation call reference library in Western Ecuador. Methods: Mist nets were used to capture bats, and reference recordings were subsequently obtained using the Anabat Swift ultrasonic detector. Echolocation pulse selection for each species was carried out using Kaleidoscope Pro 5.6.8 and BatSound 4.2.1, measuring the following spectral and temporal parameters of the echolocation signals in the search phase: initial, final, and maximum energy frequency, pulse duration, and interpulse interval. Results: N. innoxius presented the echolocation signals with the greatest variability of the spectral and temporal parameters, emitting pulses with high modulation speed (with one prominent FM component), and of low modulation speed (with one prominent QCF component); M. nigricans emissions were characterized by broadband signals of very short duration; and M. molossus presented alternation in its echolocation signals, where both high and low pulses had very little variability. Conclusions: The acoustic description of an endangered species like N. innoxius alongside the descriptions of other species frequently detected at the same study site, contributes to the construction of a bat echolocation call reference library. This input is the basis of future research of the ecology and behavior of the insectivorous bats that inhabit the Western Ecuador, which in turn is very valuable for designing tools and strategies for bat conservation.